Mastering mental ray : rendering techniques for 3D and CAD professionals. - O'Connor, Jennifer, ....- (Indianapolis : Wiley, 2010)
If you're a busy artist seeking high-end results for your 3D, design, or architecture renders using mental ray, this is the perfect book for you. It distills the highly technical nature of rendering into easy-to-follow steps and tutorials that you can apply immediately to your own projects. The book uses 3ds Max and 3ds Max Design to show the integration with mental ray, but users of any 3D or CAD software can learn valuable techniques for incorporating mental ray into their pipelines. Takes you under the hood of mental ray, a stand-alone or bundled product that is often used with 3D or CAD software in the creation of movies, games, architectural renders, and television Focuses on only the most pertinent tools and techniques for busy professionals who need to quickly apply them on the job Provides compelling, practical tutorials so you can start incorporating mental ray into your own production pipelines Includes a DVD with step-by-step videos to help drive home concepts and techniques Learn effective mental ray techniques with this great guide, then keep this practical book at your workstation for reference while you work!